The Recognition, Incidence, and Management of Spinal Cord Monitoring Alerts in Pediatric Cervical Spine Surgery. Issue 10 (November 2018) - Mohammad, Waleed; Lopez, Denise; Isley, Michael; Phillips, Jonathan H.
Abstract : Background: Perioperative spinal cord injury and postoperative neurological deficits are the major complications in spinal surgery. Monitoring of spinal cord function is of crucial importance. Somatosensory evoked potentials and transcranial electric motor-evoked potentials are now widely used in cervical spine surgery. Although much has been written on spinal cord monitoring in adult spinal surgery, very little has been published on the incidence and management of monitoring of cervical spine surgery in the pediatric population. The goal of this research was to review the recognition, incidence, and management of spinal cord monitoring in pediatric patients undergoing cervical spine surgery over the course of twenty years in a single institution. We postulate spinal cord monitoring alerts in pediatric cervical spine surgery are underreported. Methods: An IRB-approved retrospective single institution review of pediatric cervical spine cases from 1997 to 2017 was performed. Both the surgeon's dictated operative note and the neuromonitoring team's dictated note were reviewed for each case, and both were cross referenced and correlated with one another to ensure no alerts were missed. All monitoring changes were assumed to be significant and reported. The incidence of alerts, type of changes, and corrective maneuvers were noted. New postoperative neurological injuries were recorded. Results: From 1997 to 2017 fifty-three patients underwent a total of 69 procedures involving the cervical spine. Fourteen procedures (20%) were not monitored, whereas 55 procedures were 80%. There were 12 procedures (21.8%) complicated by neuromonitoring alerts. Conclusions: The number of cases complicated by alerts doubles that previously reported, and it is important to note there were no new permanent neurological deficits recorded over the study period. Corrective strategies were implemented once the operating surgeon was notified of the neuromonitoring alert. Aborting the case was then considered if corrective strategies failed to restore baseline neurophysiology. Level of Evidence: Level IV.